Commodity risk assessment of Malus domestica plants from United Kingdom - EFSA Panel on Plant Health (PLH Panel); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal, 2023)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘High risk plants, plant products and other objects’. This Scientific Opinion covers plant health risks posed by rooted plants in pots, bundles of bare‐rooted plants or trees and bundles of budwood and graftwood of Malus domestica imported from the United Kingdom, taking into account the available scientific information, including the technical information provided by the United Kingdom. All pests associated with the commodities were evaluated against specific criteria for their relevance for this opinion. Two quarantine pests (tobacco ringspot virus and tomato ringspot virus), one protected zone quarantine pest (Erwinia amylovora) and four non‐regulated pests (Colletotrichum aenigma, Meloidogyne mali, Eulecanium excrescens, Takahashia japonica) that fulfilled all relevant criteria were selected for further evaluation. For E. amylovora, special requirements are specified in Commission Implementing Regulation (EU) 2019/2072. Based on the information provided in the Dossier, the specific requirements for E. amylovora were met. For the remaining six pests, the risk mitigation measures proposed in the technical Dossier from the UK were evaluated considering the possible limiting factors. For the selected pests, expert judgement is given on the likelihood of pest freedom, taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The degree of pest freedom varies among the pests evaluated, with scales (E. excrescens and T. japonica) being the pests most frequently expected on the imported budwood and graftwood. The Expert Knowledge Elicitation indicated with 95% certainty that between 9,976 and 10,000 bundles (consisting of 50 up to 500 plants each) per 10,000 would be free from the above‐mentioned scales.